An Analysis of Teacher Talk in a Senior High School in Palu, Central Sulawesi through the Use of Self-Evaluation of Teacher Talk (SETT) - Moh. Abraham Akbar Eisenring; Margana Margana (Pascasarjana UM, 2018)
Abstract: This present research tended to analyze the teacher talk performed by the English teachers in a Senior High School in Palu, Central Sulawesi through the use of Self-Evaluation of Teacher Talk (SETT). This research employed a case study research design, in the nature of qualitative research. Random sampling technique was used in determining the research’s participants. From the results of the research, it was found that the English teachers implemented all of the fourteen interactional strategies of SETT. Besides, the teachers and students’ perceptions were also investigated.Key Words: classroom interaction, teacher talk, interactional strategies, self-evaluation of teacher talk, perception Abstrak: Penelitian ini bermaksud untuk menganalisis perkataan guru yang dilakukan oleh guru-guru Bahasa Inggris di sebuah Sekolah Menengah Atas di Palu, Sulawesi Tengah melalui penggunaan Self-Evaluation of Teacher Talk (SETT). Penelitian ini menggunakan desain penelitian studi kasus, yang berada di dalam naungan penelitian kualitatif. Teknik random sampling digunakan untuk menentukan para peserta penelitian. Berdasarkan hasil penelitian, ditemukan bahwa guru-guru Bahasa Inggris melakukan ke-14 strategi berinteraksi yang ada pada SETT. Selain itu, persepsi-persepsi guru-guru dan siswa juga diselidiki.Kata kunci: interaksi kelas, perkataan guru, strategi berinteraksi, self-evaluation of teacher talk, persepsi